2022
DOI: 10.1101/2022.05.06.22274781
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

ArcticAI: A Deep Learning Platform for Rapid and Accurate Histological Assessment of Intraoperative Tumor Margins

Abstract: Successful treatment of solid cancers relies on complete surgical excision of the tumor either for definitive treatment or before adjuvant therapy. Radial sectioning of the resected tumor and surrounding tissue is the most common form of intra-operative and post-operative margin assessment. However, this technique samples only a tiny fraction of the available tissue and therefore may result in incomplete excision of the tumor, increasing the risk of recurrence and distant metastasis and decreasing survival. Re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
3
2

Relationship

3
2

Authors

Journals

citations
Cited by 5 publications
(10 citation statements)
references
References 86 publications
0
10
0
Order By: Relevance
“…However, cutting additional tissue sections could introduce further bottlenecks when using AI tools for intraoperative assessment. Yet, some prior research has suggested that AI might expedite the decision on when to section blocks 6,21,22 . The prevalence of low‐quality sections can differ among institution, thus influencing their impact.…”
Section: Discussionmentioning
confidence: 99%
See 4 more Smart Citations
“…However, cutting additional tissue sections could introduce further bottlenecks when using AI tools for intraoperative assessment. Yet, some prior research has suggested that AI might expedite the decision on when to section blocks 6,21,22 . The prevalence of low‐quality sections can differ among institution, thus influencing their impact.…”
Section: Discussionmentioning
confidence: 99%
“…For example, previous studies have shown that suboptimal specimen quality, like fragmented tissue samples, has limited impact on identifying positive margins. This is partly because it signals the Mohs surgeon to possibly extract additional sections from the tissue block or resected tissue for a more comprehensive evaluation 6,16 . However, cutting additional tissue sections could introduce further bottlenecks when using AI tools for intraoperative assessment.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations